Tax reform and the cost of capital - Jorgenson, Dale W. (Dale Weldeau), 1933-; Yun, Kun-Young.; Oxford eBooks (Oxford : Clarendon Press, 1991)
The first of a set of lectures inaugurated by the University of Uppsala and given every two years in honour of the Swedish economist Erik Lindahl. The lectures in this volume survey the new theoretical links between monetary theory and public finance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Income tax -- Mathematical models; Corporations -- Taxation -- Mathematical models; Capital -- Mathematical models; Capital investments -- Mathematical models; Corporations -- United States -- Taxation -- Mathematical models; Electronic books